Proceedings of the 2007 Conference on Applications, Technologies, Architectures, and Protocols for Computer Communications 2007
DOI: 10.1145/1282380.1282424
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and mitigating the impact of RF interference on 802.11 networks

Abstract: We study the impact on 802.11 networks of RF interference from devices such as Zigbee and cordless phones that increasingly crowd the 2.4GHz ISM band, and from devices such as wireless camera jammers and non-compliant 802.11 devices that seek to disrupt 802.11 operation. Our experiments show that commodity 802.11 equipment is surprisingly vulnerable to certain patterns of weak or narrow-band interference. This enables us to disrupt a link with an interfering signal whose power is 1000 times weaker than the vic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(104 citation statements)
references
References 11 publications
1
96
0
3
Order By: Relevance
“…Traditionally, channel hopping and link adaptation techniques have been developed as solutions that mitigate the effect of jamming [13,14,15,16,17,18,19]. Channel hopping techniques attempt to avoid jammed channels through changing the channel among the orthogonally available channel bands.…”
Section: Jamming Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, channel hopping and link adaptation techniques have been developed as solutions that mitigate the effect of jamming [13,14,15,16,17,18,19]. Channel hopping techniques attempt to avoid jammed channels through changing the channel among the orthogonally available channel bands.…”
Section: Jamming Mitigationmentioning
confidence: 99%
“…A pair of nodes using proactive channel hopping has a hopping sequence that periodically changes [14]. In a reactive channel hopping scheme, a node only switches to a different channel if it detects the presence of jamming signal [13,15,16,18]. If a coordinator or pair of nodes decides to switch channels, all other nodes in the network switch channels as well.…”
Section: Jamming Mitigationmentioning
confidence: 99%
“…While most studies focus on the analysis of ZigBee performance degradation in the presence of WiFi interference, recently, it has been shown that significant throughput reductions can also be observed in WiFi networks [3,9]. Surprisingly, WiFi vulnerabilities arise despite the fact that many mechanisms have been included at the medium access control (MAC) and physical (PHY) layer to guarantee robustness to interference.…”
Section: Related Workmentioning
confidence: 99%
“…A large body or prior studies employ frequency hopping (FH) techniques to overcome the presence of jammers [26][27][28]. Frequency hopping can be either proactive or reactive.…”
Section: Jamming In Wireless Networkmentioning
confidence: 99%
“…To the best of our knowledge, FIJI is the first system to examine the effects of implicit jamming on the overall performance of WLANs and mesh networks. Gummadi et al [26] find that 802.11 devices are vulnerable to specific patterns of narrow-band interference related to time recovery, dynamic range selection and PLCP-header processing. They show that due to these limitations, an intelligent jammer with a 1,000 times weaker signal (than that of the legitimate transceiver) can still corrupt the reception of packets.…”
Section: Previously Proposed Anti-jamming Techniquesmentioning
confidence: 99%